2014
DOI: 10.5334/jeps.cj
|View full text |Cite
|
Sign up to set email alerts
|

What Is Lost During Dreamless Sleep: The Relationship Between Neural Connectivity Patterns and Consciousness

Abstract: Non-rapid eye movement (NREM) sleep is characterised by reduced consciousness; thus, studying its neural characteristics acts as a useful indication of what is needed for conscious experience. The integrated information theory (Tononi, 2008) states that the ability of different thalamocortical regions to interact is crucial for consciousness, thereby motivating research concerning connectivity changes in the thalamocortical system that accompany changing consciousness levels. This review aims to discuss invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, during N2 and N3 stages, males showed stronger frontal-central synchronization predominance in delta and theta bands, but weaker in beta band, while there were no sex differences in alpha band. As N1 sleep stage represents the transition between wakefulness and sleep, it is considered 'unstable sleep' [52]. When subjects were awakened from N1 stage, they often report dream-like experiences or claim they were awake [53].…”
Section: B Sex Differencesmentioning
confidence: 99%
“…However, during N2 and N3 stages, males showed stronger frontal-central synchronization predominance in delta and theta bands, but weaker in beta band, while there were no sex differences in alpha band. As N1 sleep stage represents the transition between wakefulness and sleep, it is considered 'unstable sleep' [52]. When subjects were awakened from N1 stage, they often report dream-like experiences or claim they were awake [53].…”
Section: B Sex Differencesmentioning
confidence: 99%
“…Often spectral and networks features elicited in SLEEP N1 were more similar to wakefulness than to NREM sleep. SLEEP N1 represents the transition between wakefulness and sleep and it is considered 'unstable sleep' (Klimova 2014). When awakened from SLEEP N1 subjects often report dream-like experiences or claim they were awake (Nir et al 2013).…”
Section: The Relationship Of Our Findings To Previous Studiesmentioning
confidence: 99%
“…Changes in cortical connectivity associated with sleep have been widely investigated in functional magnetic resonance (fMRI) studies, but their relationship with consciousness remains unclear (Klimova 2014). Results point to a general impairment of functional connectivity in the thalamocortical system (Spoormaker et al 2010(Spoormaker et al , 2012; in particular, long-range connectivity was shown to be affected by sleep (Tagliazucchi et al 2013) and connectivity networks in NREM sleep show increased local clustering when compared to wakefulness .…”
Section: Introductionmentioning
confidence: 99%